Perkembangan Entrepreneur di Malang: Studi Proses, Fase Perkembangan, dan Model yang Berkelanjutan - Armanu, Armanu; Novadjaja, Lily Hendrasti; Noermijati, Noermijati (Jurnal Aplikasi Manajemen, 2011)
The study aims to describe (1) the creation process of entrepreneur, (2) the entrepreneur development face, and (3) the sustainable entrepreneur model. Qualitative approach with fenomenological method were utilized to get the description. The study found that (1) the entrepreneur was created through family life and work experiences; (2) the entrepreneur development process through product innovation, process innovation and marketing innovation, and (3) strengtherning "high intention to their son and doughter for being an entrepreneur is needed to be a model of sustainable entrepreneur.